Experimental Investigation of the Impact of Using Alcohol-Biodiesel-Diesel Blending Fuel on Combustion of Single Cylinder CI Engine - H. M., Mahmudul; Hagos, F. Y.; R., Mamat; Abdul Adam, Abdullah; Awad, Omar I. (IOP Publishing, 2016)
The effect of alcohol addition has been experimentally in vestgated in the current study by blending it with diesel and palm based biodiesel on the combustion of a compression ignition engine. The experiment was run by single-cylinder, naturally aspirated, direct injection, four-stroke diesel engine. Based on the pressure-crank angle data collected from the pressure transducer and crank angle encoder, the combustion analysis such as incylinder pressure, incylinder temperature, energy release rate, cumulative energy release and ignition delay are analysed. In this comparative study, the effects of alcohols namely butanol BU20 (20% butanol addition on the commercially available diesel biodiesel emulsion) is compared and evaluated with pure diesel (D100). The results revealed that the the ignition delay for BU20 is longer as compared to that of D100 in all engine speeds and loads compared. Besides, the incylinder temperatures were rudecued with the butanol addition. The energy release rate for BU20 was higher than that for diesel, whereas the peak positions concerning the energy release rate for BU20 was discovered at 2400 rpm. Therefore addition of butanol will have positive role on the NOx emissions and stability of the engine due to its higher latent heat of vaporization.